2023
DOI: 10.1093/cid/ciac984
|View full text |Cite
|
Sign up to set email alerts
|

Three-Day Icatibant on Top of Standard Care in Patients With Coronavirus Disease 2019 Pneumonia: A Randomized, Open-Label, Phase 2, Proof-of-Concept Trial

Abstract: Background We aimed to evaluate icatibant, a competitive antagonist of the bradykinin B2 receptors, for the treatment of inpatients with COVID–19 pneumonia admitted in the early hypoxemic stage. Methods The randomized, open–label clinical trial of icatibant for COVID–19 pneumonia (ICAT·COVID, registered as NCT04978051 at ClinicalTrials.gov) was conducted in Barcelona. Inpatients requiring supplemental but not high–flow oxygen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…However, only retrospective data from patients requiring continuous positive airway pressure support ( 41 ) and a single phase 3 trial reported a survival benefit when administering an anti-C5a antibody, albeit in mechanically ventilated COVID-19 patients for the latter ( 42 ), whereas another large phase 3 trial in the same population using a C5 inhibitor was futile ( 43 ). Clinical trials targeting the CAS and KKS are scarce, and consist of small sample sizes ( 44 , 45 ). In the only published randomized controlled trial of C1INH in COVID-19, C1INH did not influence clinical improvement and length of stay compared to the SOC arm, in line with our study results ( 46 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, only retrospective data from patients requiring continuous positive airway pressure support ( 41 ) and a single phase 3 trial reported a survival benefit when administering an anti-C5a antibody, albeit in mechanically ventilated COVID-19 patients for the latter ( 42 ), whereas another large phase 3 trial in the same population using a C5 inhibitor was futile ( 43 ). Clinical trials targeting the CAS and KKS are scarce, and consist of small sample sizes ( 44 , 45 ). In the only published randomized controlled trial of C1INH in COVID-19, C1INH did not influence clinical improvement and length of stay compared to the SOC arm, in line with our study results ( 46 ).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, increased vascular permeability during experimental hantavirus infection can be prevented with drugs that block BK binding [ 78 ]. Icantibant, in fact, may be a useful therapy in various infections since adding it to standard care improved both COVID-19 pneumonia and mortality in a very recent proof-of-concept study [ 79 ].…”
Section: Role Of Different Factors In the Variationmentioning
confidence: 99%
“…Of interest, many recent clinical trials are assessing the use of Icatibant in treating other diseases. In a phase 2 clinical trial conducted in Barcelona by Malchair et al, they found that Icatibant improved mortality and pneumonia in patients with COVID-19 when a three-day Icatibant was added to the standard care of COVID-19 [ 51 ]. In another RCT by Gamboa et al, they found that continuous infusion of icatibant during hemodialysis prevented blood pressure decrease in patients complaining of intradialytic hypotension compared to placebo.…”
Section: Reviewmentioning
confidence: 99%